A Review on Drinking Water Treatment with Disinfectant (International Journal of Innovative Research in Computer Science & Technology, 2022)
The majority of the world's natural water  sources are not always safe to consume untreated. Raw  water from rivers, lakes, ponds, and groundwater can  include microorganisms. Waterborne diseases can be  contracted by consuming it when pathogens in the water are  spread through a drinking water distribution system. As it  guarantees that water is free of dangerous microorganisms  that cause water-borne diseases, disinfection is an essential  water treatment technique. Different disinfection techniques  are used to inactivate germs to fight waterborne illnesses.  The primary goal of this essay is to describe various  disinfection techniques, their applicability, limitations, and  factors affecting the disinfection process. Chlorine by products and the effects of chlorine by products on people.
Keywords: Raw Water; Disinfection; Pathogens; Chlorine by Products and Distribution System